Evaluating well-being: Quality of life in elderly dementia patients in Mayo hospital Lahore - Saira Afzal; Muhammad Awais; Naila Bajwa; Meha Siddiqui; Isma Haleem; Alishba Rasool; Ammad Waheed Khan; Hussain Mehmood (Journal of the Pakistan Medical Association, 2026)
Objective: To determine the quality of life and its association with sociodemographic variables in elderly people suffering from dementia. Method: The cross-sectional study was conducted at the Neurology Department of Mayo Hospital, Lahore, Pakistan, from July 15 to November 20, 2024, and comprised diagnosed dementia patients of either gender aged at least 65 years. The patients were categorised into early, middle and late stages based on their symptomatology as per the World Health Organisation guidelines. The quality of life was determined by using the short version of World Health Organisation Quality of Life questionnaire. The association between stages of dementia and quality of life scores was explored. Data was analysed using SPSS 24. Results: Of the 120 patients with mean age 70.74±5.7 years, 66(55%) were males, 50(41.7%) were illiterate, 68(56.7%) had early-stage dementia, 28(23.3%) had middle-stage dementia and 24(20%) had late-stage dementia. Stages of dementia had a significant association with quality of life (p=0.001) and health satisfaction (p=0.001). Conclusion: Dementia significantly impacted quality of life across all stages. Key Words: Quality of life, Dementia, Stages of dementia, elderly population, WHOQOL-BREF.